Un outil pour évaluer la lutte contre les inégalités femmes-hommes dans les entreprises : retour sur la construction de la base de données CAGE - Anne-Sophie Bruno; Ylenia Curci; Nathalie Greenan (Humanités Numériques)
This data paper outlines the various stages of the construction of the CAGE (Collective Agreements for Gender Equality) database. The database captures, for a representative sample of French companies, a comprehensive array of information on the actors and the negotiation processes on gender equality but also, and this aspect is more innovative, on the contents of the agreements or action plans signed on this topic at both the company and branch level. This article serves as a guide to the statistical information available on collective bargaining, offering valuable insights for researchers interested in utilising the administrative and survey data employed in this project. Additionally, it represents an opportunity to assess the uses of text mining techniques on unstructured data.